Differences in fermentation time and various rumen liquids on the nutrient content and tannins of Calliandra leaves (Calliandra calothyrsus) - Uswatun Hasanah; Devandra; Ma’ruf Tafsin (Indonesian Journal of Agricultural Research)
Fermentation is one way to lower tannin levels and improve nutritional quality. The purpose of this study is to determine the effect of fermentation time and various rumen liquids on the nutrient content and tannins of Calliandra leaves. In this study, two factors were used, namely Factor 1 of fermentation time (L1:0 day, L2: 7 days, L3: 14 days) and Factor 2 of various types of rumen liquids (C1: sheep, C2: cattle), which were compiled in a Factorial Complete Random Design. The factors observed were crude protein, crude fiber, crude fat, and tannins. Based on the results, the interaction of Calliandra leaves fermentation using different fermentation time and rumen liquid had a very real influence (P<0.01) on the average value of crude protein (20.03-25.13%), crude fiber (9.27-12.84%), crude fat (0.97-1.80%), and tannins (23.22–36.65 TAE mg/g). Based on the results of this study, C1L3 and C2L3 which have crude protein content of 22.18% and 25.13%, respectively, crude fiber content of 9.84% and 11.44%, and crude fat content of 1.80% and 1.25% are the most ideal treatment combinations. However, with tannin levels of 2.32% and 3.19%, sheep rumen liquid has been proven to be more successful in reducing tannin levels than bovine rumen liquid.